Comparative assessment of moringa oleifera seed extract and aluminum sulfate solution efficiency as coagulants for storm water treatment - Bate, Garba Barde; Adeleye, Adeniyi Olarewaju; Amoo, Afeez Oladeji; Ijanu, Emmanuel Madu; Asaju, Catherine Iyabo; Mohammed, Haruna Sale (Journal of Bangladesh Academy of Sciences, 2023)
Chemical coagulants used in water treatment are detrimental to human health. This research assessed the viability of Moringa oleifera (MO) seed extract compared with Aluminium Sulphate (Alum) as coagulants for treating stormwater. Five hundred mL of each of the eight storm water samples were analyzed through the Jar test method and zone settling rate experiment. Temperature, pH, conductivity, turbidity, and total suspended solids were assessed before and after adding the coagulants. Results obtained on the percentage reduction in interface height show lesser percentages (0.47, 0.76, 1.14, and 0.19%) when varying concentrations (50, 60, 70, and 80 mg/L) of MO seed extract were employed compared to the superior reduction percentages (87.07, 90.09, 95.27 and 94.57%.) when the same varying concentrations of Alum solution were added. Nonetheless, the percentage reduction in interface heights of the coagulants are significantly (p<0.05) different from each other. J. Bangladesh Acad. Sci. 47(1); 119-125: June 2023